Financing small businesses in France - Michel Dietsch (EIB Papers, 2003)
This paper explores empirically the effect of consolidation in the French banking industry and of Basel II on the availability of credit for small and medium-sized enterprises (SMEs). Consolidation has been associated with an increase in the number of banks the average firm borrows from and this has improved credit availability. Furthermore, the paper shows, for France, that the current Basel II proposal would result in lower capital charges on SME loans due to portfolio diversification effects and low default correlations of SMEs. It also argues that the current Basel II proposal is conservative: capital charges could be even lower if they were based on our estimates of SME loan portfolio risk. Overall, in France, credit rationing of SMEs does not seem to be a serious problem and Basel II is unlikely to hold back SME lending.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Frankreich